Pemberdayaan Masyarakat Desa Dudakawu Menuju Mandiri dan Berdaya Saing melalui Program Desa Wirausaha: indonesia - Febriansyah, Ahmad Diva; Bayu, Muhammad Bayu Nugroho; Sarwido, Sarwido; Septiarani, Diva Herninda; Prasetyo, Doni Agung; Akhis, Muhammad Ilma Akhis; Maknun, Muhammad Jauharul; Almajid, Ahmad Afan; Zahira, Tiara; Raffi, Muhamad Faizal; Putra, Fadhil Athalah; Pangestu, Binar Ageng Raganta; Haq, Muhammad Izzul; Hartoyo, Nindiya Ika Nugraha; Agustina, Hera Khilya; Ilma, Safira Putri Zidni (UII, 2025)
Located in Kembang Subdistrict, Jepara Regency, Dudakawu Village possesses significant economic potential. However, its development is hindered by challenges such as inadequate entrepreneurial skills, ineffective marketing strategies, and limited access to digital technology. To overcome these issues, the PPK Ormawa Team of the Student Executive Board from the Faculty of Science and Technology at Unisnu Jepara initiated the